Financial Analysis of Eritrean Commercial Bank: CAMEL Model - Tewelde, Hosie G.; Kiflemariam, Hewan; Aregawi, Natnael; Ghirmay, Surafiel (International Finance and Banking, 2024)
Research on Eritrean banking system is scant. Hence, this study’s aim is two-fold. To add literature to this scarce body of knowledge and to initiate the CAMEL model in the Eritrean context. The main purpose of this paper is to evaluate the performance of the Commercial Bank of Eritrea (CBER) using CAMEL approach. Data are gathered from consolidated financial statements of CBER. The analysis extends for 15 years starting from 2001 up to 2015 by employing two variables from each CAMEL parameter. Based on the selected CAMEL metrics the empirical analysis depicted a satisfactory result but with significant volatilities. Except for Capital Adequacy which is probably tied to its ownership structure Asset Quality, Management Efficiency, Earnings and Liquidity portrayed reasonable outcomes, nonetheless with frequent head and shoulder trends. These sheds light on the strengths and vulnerabilities of the bank, underlining the need to bolster the concerns of the decision makers to improve and increase its soundness.